Effects of dietary Quillaja saponin and kappa-carrageenan on growth, hypoosmotic resistance, and transcriptome of the black tiger shrimp Penaeus monodon postlarvae (Fabricius, 1798) - Jumah, Yashier Upling (2021.)
Acute salinity stress happens unnoticed in shrimp ponds, and there is a need to protect the animals by providing dietary functional ingredients that will elicit resistance to this stress. Kappa-carrageenan ( k-CGN), a sulfated polysaccharide from red seaweed, promotes against pathogen and environmental stress resistance in vitro and in vivo in shrimps. Thus, the present study evaluates the k-CGN potential as a growth-promoter and its resistance effects against salinity stress. There were three separate experiments done: (a) an attractability test; (b) a 30-day feeding trial to determine optimal inclusion of k-CGN, and (3) an acute salinity stress test. The attractability tests showed that all the experimental diets did not differ in their palatability to the shrimps (p.0.05). In the feeding trial, five groups of post-larval shrimp were fed with five experimental diets containing various inclusion levels of k-CGN, namely, 0.0, 0.15, 0.30, 0.45, and 0.60 g kg⁻¹. Results showed that the final average body weight (FABW), weight gain (WG), specific growth rate (SGR), and feed conversion efficiency (FCE) values of shrimps in the 0.15 and 0.3 g kg⁻¹ were significantly higher than that of the control group; the values of those in 0.45 and 0.60 g kg⁻¹ groups were not significantly different from those of the control group. Protein efficiency ratio (PER values, in contrast, were not significantly different from each group. The optimal inclusion level in the diet of k-CGN was 0.29 g kg⁻¹. In the acute salinity stress test, five groups of shrimps were fed with the same five experimental diets as those in the feeding experiment for two weeks, transferred them from 21 ppt salinity media to 4 ppt. Results showed that the control group exhibited a significantly highest mortality rate while in the 0.6 g kg⁻¹ group was the loudest; each group was the lowest; each group was significantly different from the other. Mortality rate decreased with increased dietary k-CGN level linearly. In conclusion, the study demonstrated that the diets containing dietary k-CGN were equally as attractive as the basal/control diet and that k-CGN showed both growth-promoting and resistance effects against acute salinity stress in the black tiger shrimp P. monodon postlarvae.
Dissertation (Doctor of Philosophy in Fisheries - Aquaculture) -- Miagao, Iloilo : University of the Philippines Visayas, May 2021.
Keywords: Sulfated polysaccharide; Refined seaweed extract